Epigenome-wide gene–age interaction study reveals reversed effects of MORN1 DNA methylation on survival between young and elderly oral squamous cell carcinoma patients - Xu, Ziang; Gu, Yan; Chen, Jiajin; Chen, Xinlei; Song, Yunjie; Fan, Juanjuan; Ji, Xinyu; Li, Yanyan; Zhang, Wei; Zhang, Ruyang (Frontiers in Oncology, 2022)
DNA methylation serves as a reversible and prognostic biomarker for oral squamous cell carcinoma (OSCC) patients. While, it is unclear whether the effect of DNA methylation on OSCC overall survival varies with age. Hence, we performed a two-phase gene-age interaction study of OSCC prognosis using Cox proportional hazards model on epigenome-wide scale. We identified one CpG probe, cg11676291MORN1, whose effect was significantly modified by age (HRdiscovery = 1.018, P = 4.07×10-07, FDR-q = 3.67×10-02; HRvalidation = 1.058, P = 8.09×10-03; HRcombined = 1.019, P = 7.36×10-10). Moreover, there was an antagonistic interaction between hypomethylation of cg11676291MORN1 and age (HRinteraction = 0.284; 95% CI: 0.135-0.597; P = 9.04×10-04). Prognosis of OSCC patients was well discriminated by the prognostic score incorporating cg11676291MORN1-age interaction (HRhigh vs low = 3.66, 95% CI: 2.40-5.60, P = 1.93×10-09). By adding 24 significant gene-age interactions using a looser criterion, we significantly improved the area under the receiver operating characteristic curve (AUC) of the model at 3- and 5-year prognostic prediction (AUC3-year = 0.80, AUC5-year = 0.79, C-index = 0.75). Our study identified a significant interaction between cg11676291MORN1 and age on OSCC survival, providing a potential therapeutic target for OSCC patients.